Multiplexed Luminex xMAP Assay for Detection and Identification of Five Adenovirus Serotypes Associated with Epidemics of Respiratory Disease in Adults - Washington, Cicely (American Society for Microbiology (ASM), 2010)
Several serotypes of human adenovirus (HAdV) cause acute respiratory disease (ARD) among healthy adults, sometimes generating broad outbreaks with high attack rates and occasional fatalities. Timely serotype identification provides valuable epidemiological information and significantly contributes to prevention (vaccination) strategies. The prevalence of specific serotypes causing ARD varies geographically. HAdV-3, HAdV-4, HAdV-7, HAdV-14, and HAdV-21 are the serotypes most commonly found in adult populations in the Western Hemisphere. Unfortunately, conventional serotype identification is a tedious process which can take a week or longer. For this reason, new molecular methods for serotype identification are needed. Commercially available rapid antigen and PCR assays for the detection of HAdV are universal but do not distinguish between the different serotypes. We describe the development of a sensitive and specific multiplex assay capable of identifying serotypes 3, 4, 7, 14, and 21. Two sets of primers were used for nonspecific (universal) PCR amplification, and serotype-specific probes coupled to Luminex tags were used for target-specific extension (TSE). PCR and TSE primers were designed using known hexon gene sequences of HAdV. The TSE products of HAdV-3, HAdV-4, HAdV-7, HAdV-14, and HAdV-21 were correctly identified using the Luminex xMAP fluid microsphere-based array system. No cross-reactivity with other respiratory pathogens or other HAdV serotypes was observed. This multiplexed assay can be expanded to include more serotypes and will allow broad and rapid detection and identification of adenoviral serotypes in a high-throughput environment.